Altered dynamic functional network connectivity in rheumatoid arthritis associated with peripheral inflammation and neuropsychiatric disorders - Lei Xie; Yanmin Zheng; Zhiduo Hou; Shuhua Ma; Zikai Huang; Jianhua Peng; Shuxin Huang; Ruiwei Guo; Jinzhuang Huang; Zhirong Lin; Zelin Zhuang; Jingjing Yin (RMD Open)
Objective This study explored the dynamic functional connective (DFC) alterations in patients with rheumatoid arthritis (RA) and investigated the correlation between the neuropsychiatric symptoms, peripheral inflammation and DFC alterations.Method Using resting-state functional MRI, we investigated the DFC based on spatial independent component analysis and sliding window method for 30 patients with RA and 30 healthy controls (HCs). The Spearman correlation was calculated between aberrant DFC alterations, Montreal Cognitive Assessment (MoCA), Hospital Anxiety and Depression Scale (HAD), C reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Diagnostic efficacy of indicators was assessed using receiver operating characteristic analysis (ROC).Results Three dynamic functional states were identified. Compared with HC, patients with RA showed reduced FC variabilities between sensorimotor network (SMN) and insula, SMN and orbitofrontal cortex, which were the crucial regions of sensory processing network. The above FC variabilities were correlated with the MoCA, HAD, CRP and ESR in patients with RA. Additionally, the CRP and ESR were negatively correlated to MoCA and positively related to HAD in patients with RA. The ROC analysis results showed that MoCA, HAD and FC variabilities of the sensory processing network could distinguish patients with RA from HC and also identify patients with RA with high ESR.Conclusion Our findings demonstrated that abnormal DFC patterns in sensory processing networks in patients with RA were closely associated with peripheral inflammation and neuropsychiatric symptoms. This indicates that the dynamic temporal characteristics of the brain functional network may be potential neuroimaging biomarkers for revealing the pathological mechanism of RA.